(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2016)
Polonskaya has created the image of T. Shevchenko in poem «Portrait». She presented her own reception of destiny and works of the poet. The content of the work shows deep knowledge of the Russian poetess not only about the fate of the Bard, but also about the culture and the history of Ukraine. She widely uses Ukrainian words and dialecticisms in the poem. The Image of Taras Shevchenko represents personal, maternal attitude of E. Polonskaya to the fate of Ukrainian poet. Despite the socialist realism of works, Russian poetess avoided monumentality in the image of T.Shevchenko, the reader together with the author sympathize with the protagonist of the poem.